Up-regulation of EP2 and EP3 receptors in human tolerogenic dendritic cells boosts the immunosuppressive activity of PGE2. Issue 3 (19th June 2017) - Flórez-Grau, Georgina; Cabezón, Raquel; Borgman, Kyra J E; España, Carolina; Lozano, Juan Jose; Garcia-Parajo, Maria F; Benítez-Ribas, Daniel
Abstract : PGE2 signals via EP2 and EP3 receptors to promote IL-10 production by tol-DCs, and potentiate their immunosuppressive properties. Abstract: Dendritic cells (DCs) are APCs essential in regulating the immune response. PGE2, produced during inflammation, has a pivotal role in the maturation of DCs and, therefore, is vital for the immune response. The large variety of biologic functions governed by PGE2 is mediated by its signaling through 4 distinct E-type prostanoid (EP) receptors. Immunogenic DCs express EP2 and EP4, which mediate the PGE2 signaling. However, the expression and function of EP receptors in human tolerogenic DCs (tol-DCs), which present an inhibitory phenotype, have not yet, to our knowledge, been assessed. To clarify the role of EP receptors in tol-DCs, we examined the expression of different EP receptors and their effect using selective agonists in human cells. We find that EP2 and EP3 expression are up-regulated in in vitro–generated tol-DCs compared with mature DCs (mDCs). Activation of EP2 –EP4 has a direct effect on the surface expression of costimulatory molecules and maturation receptors, such as CD80, CD83, and CD86 or MHCII and CCR7 in tol-DCs, the latter being exclusively modulated by PGE2 –EP4 signaling. Importantly, we find that EP2 and EP3 receptors are involved in tolerance induction through IL-10 production by tol-DCs. These results are in sharp contrast with the inflammatory role of EP4 . Moreover, we show that DCs generated in the presence of agonists for EP receptors, induce naive T cell differentiation toward polarized Th1/Th17 cells. Given the differential effects of EP receptors, our results suggest that EP receptor agonist/antagonists might become relevant novel drug templates to modulate immune response.